ANALISIS KEBUTUHAN GURU KIMIA TERHADAP MATERIAL KURIKULUM MODEL â€œATKâ€ DAN POLA EDUKASI â€œADIRâ€ - Rosbiono, Momo (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2011)
This research initiated from the problems there are low quality of chemistry teacher comprehend in academic knowledge. The main goals of this research was to comprehend what model of â€Curriculum Materialsâ€ (CM) and â€œAmalgamation Teacher Knowledgeâ€ (ATK) educative framework were needed by chemistry teacher?. The research conducted by using descriptive method which express phenomenon are there him. The subject of this research were the Candidate of Chemistry Teachers which out-going in program of Profession Training and Education (PTE) at Department of Chemistry Education, Faculty of Mathematics and Science Education, Indonesia University of Education and Chemistry Teachers from Group Discussion of Chemistry Teacher (GDCT) at Karawang. The data were collected through questionnaires and analysis form of teacher academic needs. The data analysis technique worked through qualitative and quantitative techniques. Based on the empirical and theoretical analysis the research findings which resulted were: (1) The CM with ATK model was relevance with academic chemistry teacher needs, this model illustrated the integration of essential concepts of curriculum, chemistry subject matter, chemistry teaching, professional development of chemistry teacher, and academic skills of chemistry teacher through â€œkey formulasâ€; (2) the CM structure that relevance for chemistry teacher academic needs was included the objectives formulation, subject matter description, questions, training tasks, and answer keys; (3) the CM content that relevance for chemistry teacher academic needs was included the essential concepts of curriculum, chemistry content, chemistry teaching, professional development of chemistry teacher, and academic skills of chemistry teacher; (4) the educative framework that effectively for using CM was guidance and training through the mechanism of â€œabsorbing, doing, interacting, and reflectingâ€ (ADIR).